Dampak Desentralisasi Pendidikan terhadap Mutu Pendidikan - Arlen; Syafitri, Ayu; Ridwal Trisoni (Jurnal Dirosah Islamiyah, 2024)
Decentralization of education has become a main topic in efforts to improve the accessibility and quality of education in various parts of the world. This article discusses the concept of educational decentralization as a strategy to overcome the challenges of a centralized education system. Decentralization of education provides opportunities for equal distribution of education and empowerment of local communities in managing learning. This study discusses the decentralization of education, which was initially completely controlled by the central government. With the decentralization of education, regional governments have the authority to regulate and control education in their regions in an effort to improve the quality of education. This research uses a qualitative approach with a literature study type. Data was collected from various journal articles and books in accordance with the research topic through content analysis. This type of research is qualitative research. The results of this study show that decentralization of education is actually implemented entirely by local governments, so that the impact can be felt by school residents in an effort to improve the quality of education.